Case Report: Freeze-Dried Human Amniotic Membrane Allograft for the Treatment of Chronic Wounds: Results of a Multicentre Observational Study - Schmiedova, Iveta; Ozanova, Zuzana; Stastna, Elen; Kiselakova, Ludmila; Lipovy, Bretislav; Forostyak, Serhiy (Frontiers in Bioengineering and Biotechnology, 2021)
An inability of the human body to heal acute wounds under certain conditions results in the formation of chronic ulcers. Chronic wounds not only cause significant pain and discomfort for patients but also serve as an entry for microorganisms into the human body, which can result in serious life-threatening problems and become a significant burden for the patients and society. The current work present results of a multicentre prospective observational study demonstrating the use of a lyophilized amniotic membrane (AM) in the treatment of chronic wounds (various etiologies). Lyophilized AM produced under the commercial brand Amnioderm® was used as an allograft material for therapy of chronic wounds, in addition to chronic ulcer standard-of-care (SoC) protocols. The duration of wounds considered for the application of AM ranged between 2 months and 11 years. In total, 16 patients were enrolled to the study, of which eight were completely healed, six demonstrated a significantly reduced ulcer size, and two did not respond to the AM therapy. The current study unambiguously demonstrates an effective alternative to the standard of chronic wound care and confirms a significant effect of the AM application for chronic wound management as a new SoC.